Digitalization of Financial Reporting Through XBRL and the Cost of Equity - Valentina Tohang; Silvi Lusiana (The Indonesian Accounting Review, 2022)
This study aims to explore the relation between the pre and post adoption of the Extensible Business Reporting Language (XBRL) adoption and the cost of equity capital in Indonesian-listed firms. The study examines 59 listed companies for four years, including two years before (2014-2015) and two years after (2016-2017) the adoption of XBRL in Indonesia. By comparing the pre and post adoption periods, the multiple regression analysis results will provide valuable information for the related stakeholders of the Indonesia Stock Exchange (IDX). Furthermore, this paper examines the impact of the control variables, such as the firm’s size, leverage, vari-ability of return, and price-to-book ratio to the relationship between XBRL and cost of equity (COE). The results show that XBRL adoption is significant in reducing the cost of equity and large-sized firms are more likely to enjoy greater reduction. This paper contributes to the research area by providing evidence on the relationship between XBRL adoption and COE in Indonesia that have mixed results in various countries and environments.